Vampire diaries : The Hunters : Moonsong / [book 9] - Smith, L. J., 1965- (Lisa Jane) (Hodder Children's Books, 2012)
Life is better than ever, Ellen and her friends can´t wait to attend Dalcrest College. But when students start to disappear from campus, suddenly ever new acquaintance is a potential enemy. Then Elena uncovers a long-hidden secret, one that shocks her to the core, she realises that darkness has followed her from Fell´s Church. But will it be Stefan or Damon who catches her when she falls?